B05 Exploring the impact of sleep on physical performance among junior soldiers in Army basic training - Ratna, Enoch; Chapman, Shaun; Liddel, Ellie; Roberts, Andrew; Rawcliffe, Alex (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Good quality sleep is essential for optimal cognitive and physical performance during basic training (BT), reducing risk of injury and preventing musculoskeletal injuries. Research shows junior soldiers (JS) still experience inadequate sleep duration and poor sleep quality throughout BT. Traditional military culture often normalises sleep restriction, being perceived as a method to ‘harden’ recruits during BT. However, evidence highlights poor sleep’s negative consequences on recovery, wellbeing and performance, emphasising the need to prioritise sleep health in military training. The aim of this study is to explore the relationship between sleep duration and physical performance among JS in BT. This was achieved by investigating the effects of extended morning wake-times on JS behaviour and performance during their 40-week course. A two-arm clustered, parallel trial with baseline data (recorded from week 1 - 10 of training) was employed to quantify the effects of extended-morning wake times of JS performance. Approved by the Ministry of Defence Research Ethics Committee, data was collected from JS from the Army Foundation College, Harrogate (AFC(H)). Morning wake time was extended by 90 min (07:00) in the intervention group (EXP; n 221, age: 16.9 ± 0.5 years) from week 11. The control group (CON; n 255, age: 17.1 ± 0.2 years) followed typical wake-times (05:30). Pseudo-objective sleep-wake indices were collected using wrist-worn actigraphy (Actigraph wGT3X-BT) each night. Online surveys captured perceptions of sleep quality, stress and daytime sleepiness during BT, which were descriptively analysed. Actigraphy sleep characteristic data was extracted using ActiLife software, processed using Excel and analysed in SPSS (v2.9). This was a preliminary analysis covering the first cohort. AFC (H) provided discipline reports and physical performance data from role fitness tests at entry (RFT(E)) and the end of BT (RFT (BT)). There were no significant differences in total sleep time (TST) or perceptual outcomes between groups at baseline (average TST EXP: 06:40 ± 0.38 mins; CON: 06:32 ± 0.36mins). Sleep duration was inadequate, and when grouped, 85% and 95% reported “poor” sleep quality and excessive daytime sleepiness, respectively. We hypothesise that extending-morning wake times will positively impact sleep duration, associated perceptual outcomes of stress and sleepiness; and result in better disciplinary and physical performance outcomes of EXP compared to CON. The baseline data supports recent literature that JS experience insufficient, poor quality sleep during training. Regarding the intervention, it is expected that extended wake-times will improve RFT performance, stress, sleep quality and daytime sleepiness.